STUDIES ON THE VEGETATION OF MEXICO V FEATURES OF THE VEGETATION OF THE WATERSHED OF THE BALSAS RIVER - MIRANDA, FRANCISCO P DE (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
M sulphuraria n sp is descr from Tabasco, Mexico
REV SOC MEX HIST NAT
Keywords: STUDIES, VEGETATION OF MEXICO V, FEATURES, VEGETATION, WATERSHED, BALSAS RIVER; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL (BOTANICA)